Design of a Triband Antenna Microstrip for 2.4 Ghz, 3.5 Ghz and 5.7 Ghz Applied a Wban - Kaschel-Carcamo, H (Institute of Electrical and Electronics Engineers Inc., 2017)
This paper presents a design of a Triband microstrip antenna for 2.4 GHz, 3.5 GHz and 5.7 GHz applied a WBAN (Wireless Body Area Network). The proposed antenna with three substrates types consists of L-shaped slots have been determined based on the frequency bands. For the integration of these techniques three frequency bands consisting of the ISM band 2.4 GHz and 5.7 GHz, and 3.5 GHz band UWB respectively were considered. The proposed antenna is designed with the purpose of obtaining a low SAR models of the human body, considering both the electromagnetic effect and the shell model in human tissues. © 2017 IEEE.